Genome-wide DNA methylation of Munro’s microabscess reveals the epigenetic regulation in the pathogenesis of psoriasis - Xu, Xiaoqing; Zhang, Yuxi; Pan, Zhaobing; Zhang, Xiaojing; Liu, Xiaonan; Tang, Lili; Zhang, Xiaoguang; Zhou, Fusheng; Cheng, Hui (Frontiers in Immunology, 2022)
Introduction Munro's microabscess is a typical pathological feature in the early psoriatic lesion, mainly characterized by the accumulation of neutrophils in the epidermis. DNA methylation microenvironment of Munro's microabscess and the crosstalk with transcription and its effect on neutrophils have not yet been revealed. Methods Performed genome-wide DNA methylation analysis and further differential methylation analysis of psoriatic skin lesions with and without Munro's microabscess from two batch samples consisting of 114 former samples in the discovery stage and 21 newly-collected samples in the validation stage. Utilized GO, MEME, and other tools to conduct downstream analysis on differentially methylated sites (DMSs). Correlation analysis of methylation level and transcriptome data was also conducted. Results We observed 647 overlapping DMSs associated with Munro's microabscess. Subsequently, GO pathway analysis revealed that DNA methylation might affect the physical properties associated with skin cells through focal adhesion and cellsubstrate junction and was likely to recruit neutrophils in the epidermis. Via the MEME tool, used to investigate the possible binding transcription factors (TFs) of 20 motifs around the 647 DMSs, it was found that DNA methylation regulated the binding of AP1 family members and the recruitment of neutrophils in the epidermis through the TGF-beta pathway and the TH17 pathway. Meanwhile, combined with our earlier transcriptome data, we found DNA methylation would regulate the expressions of CFDP, SIRT6, SMG6, TRAPPC9, HSD17B7, and KIAA0415, indicating these genes would potentially promote the process of Munro's microabscess. Discussion In conclusion, DNA methylation may affect the course of psoriasis by regulating the progression of Munro's microabscess in psoriatic skin lesions.